Tax Reliefs for Innovation after the Polish Deal − An Attractive Solution for Polish Entrepreneurs? A Pilot Study - Janiszewska, Magdalena; Janiszewski, Jan M. (Ulgi podatkowe na innowacje po Polskim Ładzie – atrakcyjne rozwiązanie dla polskich przedsiębiorców? Badania pilotażowe, 2025)
Aim: On 1 January 2022, “The Polish Deal” policy introduced a number of new tax reliefs regarding robotization, innovative employees and prototypes, which supplemented the current system of incen-tives for innovation and amended those already existing (R&D relief and IP Box). The aim of the article was to verify the attitudes of Polish entrepreneurs towards the introduced legislative changes and to identify barriers in their application. Methodology: In order to achieve the research goal, literature and questionnaire-based pilot studies were carried out. The respondents were asked questions concerning their innovation activities, tax incentives already used and planned by them for the future, as well as their opinions about the discussed tax reliefs and the barriers in their application. The authors used the 5-point Likert scale. Results: The research results demonstrated that the introduction of tax reliefs was assessed by the respondents as a positive phenomenon; however, the shape of the regulations implemented in 2022 did not encourage the vast majority entrepreneurs to apply them in practice. Implications and recommendations: The provisions introduced so far have significant potential for improvement in terms of the degree of their precision, transparency and requirements related to their application. On the other hand, frequent changes in tax law inhibit the development of innovative activity, therefore the new regulations should not only be transparent and precise but also stable, and designed to be long-lasting.Originality/value: The empirical research on attitudes of Polish enterprises towards tax reliefs for innovation after the legal changes in 2022 fills the research gap in this area.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 1, s. 59-70
Keywords: innovation; tax reliefs; polish entrepreneurs; Polish Deal; innowacje; ulgi podatkowe; polscy przedsiębiorcy; Polski Ład